PENGELOLAAN DAN KESEHATAN LINGKUNGAN DI SEKOLAH BERASRAMA SMAN CAHAYA MADANI BANTEN BOARDING SCHOOL, KABUPATEN PANDEGLANG, BANTEN - Sarah Aphirta; Sintorini Moerdjoko; Rositayanti Hadisoebroto; Hilarion Widyatmoko; Qurrotu Aini Besila; Hera Trihidayanti; Milani Yolanda Salim (Universitas Trisakti, 2022)
Environmental health is a very important element in relation to the potential for the spread of disease, especially in the era of the Covid-19 pandemic, this is happen when environmental conditions are not feasible. Through good environmental management accompanied by regular and continuous education for the residents of this limited environment, boarding school can become an example of the application of good environmental health management. Through this outreach activity, the Community Service Program of the Environmental Engineering and Landscape Architecture Study Program aims to educate the academic community of SMAN CMBBS in order to increase awareness in meeting proper basic facilities and implementing an integrated environmental health pattern by implementing clean and healthy living behaviors. The method used is a counseling of educational materials and posters through online seminars using video conference. For now, as many as 51.9% of seminar respondents do not have the readiness to restart offline learning process because there is no proper preparation from the school regarding an integrated environmental health management system in preventing the formation of a pandemic cluster. The implications of this PkM activity are very useful in increasing insight and awareness of the CMBBS academic community in facing the offline learning process.